A Spelling Paradigm With an Added Red Dot Improved the P300 Speller System Performance - Wu, Yan; Zhou, Weiwei; Lu, Zhaohua; Li, Qi (Frontiers in Neuroinformatics, 2020)
The traditional P300 speller system uses the flashing row or column spelling paradigm. However, the classification accuracy and information transfer rate of the P300 speller are not adequate for real-world application. To improve the performance of the P300 speller, we devised a new spelling paradigm in which the flashing row or column of a virtual character matrix is covered by a translucent green circle with a red dot in either the upper or lower half (GC-RD spelling paradigm). We compared the event-related potential（ERP）waveforms with a control paradigm (GC spelling paradigm), in which the flashing row or column of a virtual character matrix was covered by a translucent green circle only. Our experimental results showed that the amplitude of P3a at the parietal area and P3b at the frontal-central-parietal areas evoked by the GC-RD paradigm, were significantly greater than those induced by the GC paradigm. Higher classification accuracy and information transmission rates were also obtained in the GC-RD system. Our results indicated the added red dots increased attention and visuospatial information, resulting in an amplitude increase of both P3a and P3b; thereby improving the performance of the P300-speller system.